2022
DOI: 10.1021/acsnano.2c02531
|View full text |Cite
|
Sign up to set email alerts
|

Discovering the Secret of Diseases by Incorporated Tear Exosomes Analysis via Rapid-Isolation System: iTEARS

Abstract: Nanoscale small extracellular vesicles (sEVs, exosomes) in tears allow us to investigate the multisignatures of diseases. However, the translations of tear sEVs for biomarker discovery and clinical diagnostics are practically limited by low recovery, long processing time, and small sample volume. Here, we report an incorporated tear-exosomes analysis via rapid-isolation system (iTEARS) via nanotechnology to discover the secrets of ocular disorders and systemic diseases. We isolate exosomes rapidly with high yi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(28 citation statements)
references
References 67 publications
0
28
0
Order By: Relevance
“…Data show that iTEARS might be used to improve the molecular diagnostics of dry eye disease, along with diabetic retinopathy. 361 There is also a possibility that iTEARS could be used to detect other neurodegenerative diseases and cancer.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Data show that iTEARS might be used to improve the molecular diagnostics of dry eye disease, along with diabetic retinopathy. 361 There is also a possibility that iTEARS could be used to detect other neurodegenerative diseases and cancer.…”
Section: Discussionmentioning
confidence: 99%
“…361 Furthermore, tears were established as another easily accessible body fluid expected to improve molecular diagnostics to diagnose ocular, neurodegenerative, and systemic diseases, as well as cancer. Thus, the study of miRNAs in tear exosomes has shown that miR-145-5p, miR-214-3p, miR-218-5p, and miR-9-5p are dysregulated during diabetic retinopathy development 361 Another possible diagnostic biomarker besides miRNAs are the exosomal mRNAs. 375,376 For example, specific features for diagnosing prostate cancer have been identified in circulating exosomal mRNA.…”
Section: Exosomal Nucleic Acids As Diagnostic Biomarkersmentioning
confidence: 99%
See 2 more Smart Citations
“…Purification of 15 mL cell culture medium with EXODUS resulted in removal of approximately 99% of protein impurities and recovery of approximately 90% of exosomes. iTEARS can rapidly isolate exosomes from small volumes of tears (~10 µL) by using EXODUS (Hu et al, 2022). This system has important implications for the establishment of the precision medicine based on tear exosomes.…”
Section: Non-contact Microfluidicsmentioning
confidence: 99%